2010
DOI: 10.1139/o09-176
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore analysis of the interaction of metal ions with prion proteins and peptidesThis paper is one of a selection of papers published in this special issue entitled “Canadian Society of Biochemistry, Molecular & Cellular Biology 52nd Annual Meeting — Protein Folding: Principles and Diseases” and has undergone the Journal's usual peer review process.

Abstract: Nanopore analysis can be used to study conformational changes in individual peptide or protein molecules. Under an applied voltage there is a change in the event parameters of blockade current or time when a molecule bumps into or translocates through the pore. If a molecule undergoes a conformational change upon binding a ligand or metal ion the event parameters will be altered. The objective of this research was to demonstrate that the conformation of the prion protein (PrP) and prion peptides can be modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…For example, in the absence of metal ions Zn-finger peptides, prion peptides from the octarepeat region and myelin basic protein will readily translocate; but in the presence of Zn(II) or Cu(II) the peptides fold into a compact structure and only bumping events are observed. [38][39][40] These results highlight the capacity of the pore to interrogate the conformation of the peptide at the instant at which it interacts with the pore.…”
Section: Nanopore Analysis Of Misfoldingmentioning
confidence: 83%
“…For example, in the absence of metal ions Zn-finger peptides, prion peptides from the octarepeat region and myelin basic protein will readily translocate; but in the presence of Zn(II) or Cu(II) the peptides fold into a compact structure and only bumping events are observed. [38][39][40] These results highlight the capacity of the pore to interrogate the conformation of the peptide at the instant at which it interacts with the pore.…”
Section: Nanopore Analysis Of Misfoldingmentioning
confidence: 83%
“…As shown previously, the proportion of Type-I events are about 60%. 37 Upon addition of antibody SN6b there was no significant change in the percentage of type-I events as would be expected if the antibody did not bind to the native protein (Fig. 1B).…”
Section: Resultsmentioning
confidence: 56%
“…35 At present these possibilities cannot be distinguished. Previously, our group has used nanopore analysis to probe various aspects of PrP C behavior, including metal binding 37 and the interaction with PrP C specific-antibodies. 35 As well, it was demonstrated that the event profiles after pre-incubation in 1.5 M guanidinium hydrochloride (Gdn-HCl) of wild-type bPrP and mutant bPrP(T194A) were different as were those of full length human PrP(23-231) and truncated PrP(90-231).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Previously nanopore analysis has allowed detailed investigation of various aspects of the PrP C structure-activity relationship including the interaction of PrP C with metal ions and characterization of the consequences of disease-associated single amino acid mutations on interaction with a therapeutic PrP Sc -antibody. [42][43][44] Accordingly nanopore analysis was a logical approach to investigate genetic polymorphisms of ovine PrP C that are associated with differential susceptibilities to scrapie infection.…”
Section: Introductionmentioning
confidence: 99%